Engaging Resistant Adolescents in Drug Abuse Treatment - Waldron, Holly Barrett (2006)
In the first phase of a two-part treatment development study, families with a treatment-resistant, drug-abusing adolescent (n=42) were offered 12 sessions of Community Reinforcement and Family Training (CRAFT). This parent-focused intervention was designed to help parents facilitate their adolescents' entry in treatment and support adolescents' subsequent behavior change and to improve parent and family functioning. In the second phase, successfully engaged adolescents (n=30) were offered 12 sessions of a multicomponent individual cognitive behavioral therapy (CBT) targeting substance use and related problem behaviors. Measures were collected at pre- and post-treatment for parents and adolescents, with an additional follow-up assessment for parents at 3-months post-treatment. Parents in the CRAFT intervention experienced a significant reduction in negative symptoms and 71% of parents were successful in engaging their resistant youth in treatment. The CBT intervention for the engaged youth was associated with a statistically significant, but not clinically significant, reduction in marijuana use.